THE EFFECT OF POLY (ETHYLENE GLYCOL) ON THE PHOTOLUMINESCENCE PROPERTIES OF CARBON DOTS FROM CASSAVA PEELS SYNTHESIZED BY HYDROTHERMAL METHODS - Permono Adi Putro; Liszulfah Roza; Isnaeni Isnaeni (Program Studi Fisika Universitas Negeri Jakarta, 2019)
Carbon dots (C-dots) have been successfully synthesized from cassava peels using the hydrothermal method. The C-dots are further passivated using poly (ethylene glycol) (PEG) with a variation of the volume of 0.5 ml, 1.0 ml, and 1.5 ml. The properties of photoluminescence C-dots before and after PEG were characterized using photoluminescence (PL) and time-resolved photoluminescence (TRPL) spectrophotometers. PEG succeeded in influencing PL C-dots properties, such as peak wavelength, PL intensity, and electron time decay. The addition of 0.5 ml of PEG to C-dots is the optimum condition and best with the peak wavelength, the PL intensity and, time decay electron is 507.52 nm, 5302 a.u, and 3.794031133 ns, respectively.